Ekspresi Ki-67 dan HER-2/neu Berhubungan dengan Derajat Histopatologik Karsinoma Payudara Invasif No Special Type (NST) - Sanggam B Hutagalung; I Ketut Mulyadi; I Gusti Alit Artha (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2014)
Background The role of Ki-67 and HER-2 /neu protein as a prognostic and predictive factor in invasive ductal breast carcinoma of no special type has been studied since the last decade. The aim of this study was to evaluate correlation between expression of Ki-67 and HER-2/neu with histopathological grade of invasive carcinoma of no special type breast. Methods This study was a cross-sectional study, which performed on paraffin embedded tissue of patients with invasive breast carcinoma of no special type who were diagnosed between Juli 2012 to September 2013. Histopathological grade was investigated by hematoxillin eosin and immunohistochemistry stain were made for Ki-67 and HER2/neu. Then the correlation between Ki-67 and HER-2/neu overexpression with histopathological grade tested by Spearman Correlation. Results We found 60 samples, mean age was 55 years old (range 28-71 years). According to histopathological grade of the tumor, we found cases of low grade were 29 cases (48.3%) and high grade were 31 cases (51.7%). There was significant positive correlation between Ki-67 overexpression and high histopathological grade of tumor r=0.650; p=0.000). There was significant correlation between HER-2/neu overexpression and high histopatho-logical grade of tumor (r=0.311; p=0.016). Conclusion It was concluded that the expression of Ki-67 and HER-2/neu have significant correlation with histopathological grade of invasive ductal breast carcinoma of no special type. Key words: HER-2/neu, histopathological grade, invasive ductal breast carcinoma no special type, Ki-67.